PENETAPAN KADAR FLAVONOID EKSTRAK RAMBUT JAGUNG MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-VIS - Gimelliya Saragih; A Zukhruf Akbari; M Zaim Akbari; Irfan Syahputra (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2021)
Indonesia is an agricultural country with extraordinary natural wealth. Indonesia is also the 6th country with the largest corn production in the world. In the city of Medan, there are many corn sellers who do not pay attention to waste from corn such as corn husks and hairs. Corn silk as one part of corn that is not used properly. Hair is just a waste that pollutes the environment. This study aims to analyze the content of corn silk so that it can be applied according to the content contained in corn silk. Corn silk was extracted using the ultrasonication method and 70% ethanol solvent for 1 hour and the thick extract was obtained using a rotary evaporator, then a phytochemical screening test was carried out to determine what secondary metabolites were contained in corn silk using UV-Vis spectrophotometry at a wavelength of 200 -400 nm The results of the phytochemical screening test showed that corn silk contained alkaloids and flavonoids. UV-VIis spectrophotometry using a standard solution of quercetin. The flavonoid content in the corn silk extract sample was 2.99%.